Correction: COVID-19 Vaccine-Induced Myocarditis and Pericarditis: Towards Identification of Risk Factors - Laura C. Zwiers; David S. Y. Ong; Diederick E. Grobbee (Ubiquity Press, 2024)
This article details a correction to: Zwiers LC, Ong DSY, Grobbee DE. COVID-19 Vaccine-Induced Myocarditis and Pericarditis: Towards Identification of Risk Factors. Global Heart. 2023; 18(1): 39. DOI: https://doi.org/10.5334/gh.1252